History of Depression and Increased Risk of Sternal Wound Infection After Cardiothoracic Surgery: A Novel and Potentially Modifiable Risk Factor. (15th February 2019) - Theodore, Deborah A; Goodwin, Renee D; Zhang, Yuan (Vivian); Schneider, Nancy; Gordon, Rachel J
Abstract: Background: Sternal wound infection (SWI) is a leading cause of postoperative disease and death; the risk factors for SWI remain incompletely understood. The goal of the current study was to investigate the relationship between a preoperative history of depression and the risk of SWI after cardiothoracic surgery. Methods: Among patients undergoing cardiothoracic surgery in a major academic medical center between 2007 and 2012, those in whom SWI developed (n = 129) were matched, by date of surgery, with those in whom it did not (n = 258). Multivariable logistic regression was used to examine the strength of relationships between risk factors and development of infection. History of depression was defined as a composite variable to increase the sensitivity of detection. Results: History of depression as defined by our composite variable was associated with increased risk of SWI (adjusted odds ratio, 2.4; 95% confidence interval, 1.2–4.7; P = .01). Staphylococcus aureus was the most common organism isolated. Conclusions: History of depression was associated with increased risk of SWI. Future prospective studies are warranted to further investigate this relationship. Depression is highly treatable, and increased efforts to identify and treat depression preoperatively may be a critical step toward preventing infection-related disease and death. Abstract : We identify history of depression as a new and significant risk factor for sternal wound infection, which is associated with substantial morbidity and mortality risk. Identifying this potentially modifiable risk factor may help decrease the incidence of sternal wound infection.